Association between the Planetary Health Diet Index and biological aging among the U.S. population - Huang, Shaoqun; Hu, Haoying; Gong, Hongyang (Frontiers in Public Health, 2024)
Background: The Planetary Health Diet (PHD) is a novel dietary pattern proposed by the EAT-Lancet Commission in 2019, yet a limited study has investigated the anti-aging effects of PHD to date. Objectives: This study aimed to explore the association between adherence to PHD, as quantified by the Planetary Health Diet Index (PHDI), and biological aging in American populations. Methods: Data were obtained from the National Health and Nutrition Examination Survey (NHANES) for 1999-2018. Food consumption information was relied on two 24-hour diet recall questionnaires. The biological aging condition was comprehensively assessed by four biological markers, including phenotypic age, biological age, telomere length, and klotho concentration. Weighted multivariate linear models, restricted cubic spline (RCS), and subgroup analysis were subsequently carried out to evaluate the influence of PHDI on biological aging. Results: 44,925 participants with complete data were finally enrolled in our study. The fully adjusted models showed decreased 0.20 years in phenotypic age [-0.20 (-0.31, -0.10)] and declined 0.54 years in biological age [-0.54 (-0.69, -0.38)] correlated with PHDI per 10 scores increment. Klotho concentration [6.2 (1.0, 11.0)] was positively related to PHDI. In Model 2, telomere length increased by 0.02 bp for every 10-point rise in PHDI. Besides, the RCS analysis results exhibited a curvilinear relationship between PHDI and four indicators.Our study explored a significant correlation between PHDI and biological aging, indicating that adherence to PHD may prevent biological aging.